Kepatuhan Terhadap Standar Bahasa Indonesia Bagi Dosen Asing Dalam Perspektif Hukum Ketenagakerjaan - Putri Asari, Talitha Faya; Pratama Herry Herlambang (Universitas Negeri Semarang, 2025)
The internationalization of higher education encourages Indonesian universities to recruit foreign lecturers to enhance academic quality and global collaboration. However, foreign lecturers must comply with legal requirements regarding Indonesian language use as stipulated in Law No. 24 of 2009, Government Regulation No. 57 of 2014, Government Regulation No. 34 of 2021, and Ministerial Regulation of Education and Culture No. 70 of 2016. These regulations mandate foreign lecturers to obtain the Indonesian Language Proficiency Test (UKBI) certificate as official proof of language competence. This study investigates the regulation and implementation of Indonesian language proficiency standards for foreign lecturers, analyzing their legal implications within employment law. Using a normative juridical approach, the research analyzes legal materials through library research, assessing norm compliance and practical implementation. Findings indicate weak enforcement of language proficiency requirements due to unclear sanctions and regulatory inconsistencies. Hiring foreign lecturers without language proficiency certification results in defective employment contracts, potential administrative penalties, and industrial relations imbalances. Furthermore, inadequate language skills among foreign lecturers negatively impact educational quality and students' rights. The study recommends harmonizing language and employment regulations, reinforcing oversight of UKBI implementation, and mandating language proficiency certification for foreign lecturer recruitment. These actions are vital to ensure legal certainty, protect local workforce rights, and uphold Indonesian as a key national language for academic and legal purposes.